Comparison of learning outcomes: Team-based vs. problem-based learning with high-Fidelity simulation in a critical care nursing course—a mixed-methods design. - Chen, Hsiu-Fang; Ho, Lun-Hui; Lee, Hsiang-Chun; Chiu, Hsiao-Feng; Tsai, Yun-Fang (Nurse Education Today, 2025)
Few studies have evaluated the comparative effectiveness of team-based learning (TBL) and problem-based learning (PBL) combined with simulation in nursing education. This study aimed to compare the learning outcomes of TBL versus PBL, incorporating high-fidelity simulation (HFS) in a critical care nursing course. This study used a mixed-methods design with convenience sampling. Senior baccalaureate nursing students from a university of science and technology were recruited. Participants were randomly assigned to the TBL or PBL group by class, each receiving their respective teaching strategies combined with HFS. Course outcomes were assessed using a variety of instruments, including a learning assessment (shock knowledge, Advanced Cardiovascular Life Support knowledge, and a final test), the Satisfaction with Simulation Experience Scale (SSES), the Confidence Scale, the Emergency Preparedness Simulation Learning Experience Scale (EPSLES), the Learning Experience Questionnaire, and a demographic questionnaire. A total of 173 senior nursing students were included. A One-way ANCOVA was utilized to control for pre-test and midterm test scores when comparing the learning effects. The analysis revealed a statistically significant difference in post-test shock knowledge scores between the two groups (F = 4.51, p = 0.04). The TBL group achieved significantly higher post-test scores compared to the PBL group. In contrast, following the HFS program, the PBL group showed significantly higher mean scores on the SSES and EPSLES than the TBL group (t = 2.09, p = 0.04; t = 2.59, p = 0.01, respectively). Our study evaluated the effectiveness of mixed teaching strategies in a critical care nursing course. Findings indicate that both TBL and PBL enhance learning outcomes. The TBL group demonstrated superior performance on the learning outcomes test, while the PBL group excelled in simulation satisfaction and emergency simulation learning experiences. These results provide insights for selecting appropriate teaching strategies in intensive care education for nursing students. • Mixed-methods using TBL or PBL with HFS can enhance nursing students' critical care learning. • TBL group scored higher in shock knowledge; PBL group favored simulation experience. • Educators help nursing students reflect, communicate, work in teams, and share outcomes.